La expansión sintáctica del verbo en catalán: propuesta de sistematización - Ginebra Serrabou, Jordi; Montserrat Ciurana, Anna (Studia Romanica Posnaniensia, 2004)
Syntactic information has been traditionally neglected in lexicographical compendia. This paper seeks to show what aspects of syntax have to be taken into account when planning a verbs dictionary and how this information can be offered systematically to guide normal users in building correct messages. To exemplify both these initial problems and how to solve them, we use the workfiles of the only dictionary on verbal information, the Diccionari d'ús dels verbs Catalans, published in 1999, of which we are the authors.